Quantification of the healthy worker effect: a nationwide cohort study among electricians in Denmark - Mikkelsen Sigurd; Hvidtfeldt Ulla A; Thygesen Lau C; Brønnum-Hansen Henrik (BMC, 2011)
Abstract Background The healthy worker effect (HWE) is a well-known phenomenon. In this study we used the extensive registration of all Danish citizens to describe the magnitude of HWE among all Danish electricians and evaluated strategies for minimizing HWE bias of the association between occupation and mortality. Methods All Danish male citizens aged 26-56 years in the period 1984-1992 were followed for three years in several registers. We evaluated HWE bias among electricians because they were unexposed to detrimental occupational exposures. We compared electricians to three reference groups (general population, construction industry and carpenters/brick layers) and utilized analytical methods for minimizing HWE bias (lag time analyses, age-stratified analyses, marginal structural model and restriction to employed, newly employed or long-term workers). Results The mortality rate was higher among electricians, who the year following active employment received incapacity benefits or were on long-term sick leave. Electricians receiving incapacity benefits, on long-term sick leave, unemployed, or with increased comorbidity index had lower odds of re-employment. Electricians had lower mortality rate (rate ratio,0.60;95%CI,0.52-0.69) compared to the general population, while electricians leaving employment had increased mortality (1.90;1.50-2.40). Adjusting for several social events slightly attenuated the estimates, while the marginal structural model did not minimize bias. Electricians had the same mortality as the construction industry and carpenters/brick layers. Mortality was comparable to the general population after three or more years of lag time. Conclusions In this nationwide study, employment as electricians had marked effect on mortality. Appropriate reference selection and lag time analyses minimized the HWE bias.